PENGARUH FUNTIONAL QUALITY, TECHNICAL QUALITY TERHADAP KEPUASAN KONSUMEN DAN WORD OF MOUTH COMMUNICATION KONSUMEN LAUNDRYNESIA - Restu Khaliq (At-Taradhi Jurnal Studi Ekonomi, 2018)
The aims of this research were to examine the effect of funtional quality and technical quality on customer satisfaction, and the effect of funtional quality, technical quality and customer satisfaction to word of mouth communication. This research have been conducted in Laundrynesia with 53 costumer on August 2018 as a respondent. Structural Equation Modeling (SEM) is used as data analysis techniques in this research. The results of the analysis prove that the variables funtional quality, technical quality have a significant influence on customer satisfaction. Funtional quality, technical quality and customer satisfaction have a significant influence too to word of mouth communication. All variable’s T-statistic value are greater than the normal t-distribution table (1,96). Funtional quality’s T-statistic value on customer satisfaction is 5,174. Technical quality’s T-statistic value on customer satisfaction is 4,753. Customer satisfaction’s T-statistic value on word of mouth communication is 10,538. Funtional quality’s T-statistic value on word of mouth communication is 3,639.  Technical quality’s T-statistic value on word of mouth communication is 4,251.